"It takes two": The interaction between parenting and child temperament on parents' stress physiology. Issue 3 (18th March 2015) - Merwin, Stephanie M.; Smith, Victoria C.; Dougherty, Lea R.
ABSTRACT: The biological basis of parenting has received recent attention given the profound effects of parenting on both child and parent health outcomes. This study examined the moderating role of child temperamental effortful control on the association between observed parental hostility and parents' cortisol awakening response (CAR), a critical index of stress system functioning. Participants included 149 parents and their preschool‐aged children. Parents obtained salivary cortisol samples at waking, and 30 and 45 min post‐waking across two consecutive days. Parental hostility was assessed during an observational parent–child interaction task, and child effortful control was assessed using parent report. Parental hostility was associated with parents' lower cortisol levels at 30 and 45 min post‐waking and lower CAR. Moreover, results demonstrated an interaction between parenting and child temperament on parent CAR. The findings highlight the need to examine the interplay between parenting and child temperament on parents' stress physiology. © 2015 Wiley Periodicals, Inc . Dev Psychobiol 57: 336–348, 2015.